(untitled) (Physical Sciences and Technology, 2017)
In this review, we try to summarize the results of experimental search and theoretical studies within variational methods, the method of Faddeev and Faddeev-Yakubovsky equations, and the method of hyperspherical harmonics for the lightest neutron and kaonic clusters. In particular, we discuss few-body neutron clusters: bineutron, trineutron and tetraneutron. Related to few-body kaonic clusters the results of calculations for binding energies and widths for the К–рр and KNNN kaonic systems are presented and discussed.